IMPACTS OF TERRORISM IN EDUCATION SECTOR DUE TO INTERNAL DISPLACEMENT: CASE STUDY CABO DELGADO- MOZAMBIQUE FROM 2017 TO 2022 - Joaquim, Isaque (Journal of Terrorism Studies, 2024)
The study aims to analyze the impacts of internal displacement in the education sector due to terrorist conflict ongoing in the northern region of Mozambique (Cabo Delgado). The internally displaced people (IDPs) in Mozambique establish themselves within the country. They abdicate their normal life and adapt themselves to the means of subsistence, and most of the time with little support from the government which does not ensure a dignified life in basic needs: education, health, and protection. This situation has been happening in the northern province of Mozambique, where access to education is deficient, mainly in rural areas. Thus, the increasing number of internal displacements puts more pressure in the access to education services. The study is only focusing in Cabo Delgado, where since 2017 people are experiencing terrorist attacks and armed conflicts resulting on an increasing number of IDPs being hosted in different provinces. The study used the technique of data collection and the analysis model aligned with the study’s purpose. This method consisted of literature review and evaluation, combined with the analysis of secondary data from different sources. The results showed that most of the IDPs are not officially registered and hosted in an officially established center of accommodation, it was difficult to know with exactitude more about other IDPs facing different challenges. This paper will help the society to know what is really happening to the education sector in Cabo Delgado, so that policy can be put in place to mitigate the risks in this sector.